Modeling and Simulation of Platform Screen Door (PSD) System using MATLAB-SIMULINK - Koc, Isa; Mermer, Omer; Kirimca, Necim; Cakir, Fatih Hayati; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2022)
In this paper, electromechanical modeling of an industrial platform screen door (PSD) system has been developed. The system incorporates several sub-units such as PMSM, motor controller, inverter, and mechanical unit. Moreover, a newly designed motor control system based on real operation conditions is introduced. In addition, modeling procedures are described, and simulation results are presented. Furthermore, numerical simulation in accordance with specific velocity and position references are provided for verifying the effectiveness of the proposed modeling. Furthermore, the results show that the developed electromechanical model of PSD system is effective in managing the parameters that affect the actual operating state of the PSD sliding door system. These modelling and simulation will play an important role in increasing the PSD design capability for real applications. © 2022 IEEE.
2022 International Conference on Data Analytics for Business and Industry, ICDABI 2022 -- 25 October 2022 through 26 October 2022 -- Virtual, Online -- 186761
Keywords: control; modeling; platform screen door; simulation; Simulink; sliding door